POLITIK HUKUM CALON TUNGGAL DALAM PUTUSAN MAHKAMAH KONSTITUSI DAN IMPLIKSASINYA TERHADAP SISTEM PILKADA SERENTAK - Yasin al Arif, Muhammad (Jurnal Yuridis, 2016)
The focus of this study is to analyze the political direction of the law of the Constitutional Court Number 100 / PUU-XIII / 2015 on a single candidate and the implications for the elections simultaneously. The formulation of the problem is first, how the legal political direction single candidate in the decision of the Constitutional Court? Second, what are the implications of the decision of the Constitutional Court against the election system simultaneously ?. Diingin achievable goal is to determine the political direction of the single candidate of law in the Constitutional Court decision and the implications of the decision of the Constitutional Court against the election system simultaneously. This research is a normative approach cases and legislation. Due to the normative research used secondary data in the form of primary legal materials, secondary law and tertiary legal materials. The study concluded that the political direction of the legal decision of this Court is to ensure the constitutional rights of citizens and to use the mechanism of "agree" and "disagree". While the implication is direct implications in the form of their new mechanisms in the implementation of the upcoming election and the Commission must simultaneously make PKPU to provide arrangements regarding the model of ballots, campaign mechanism and the mechanism of logistics division. While the indirect impact in the form of a vacuum in the law for a single candidate in the elections in order laksanan quo law and legal vacuums settings for a single candidate election disputes